New Dimension of Tourism in the Era of New Media in Oman A Case Study based on Salalah (Global Journal of Human-Social Science, 2019)
In the era of new media people and societies across the globe are interconnected and extending the new framework to business trade and tourism Different websites and social media are facilitating a plethora of content and information through photos videos 3D visualization to satisfy people s queries to promote and brand nations Due to this tourism is also witnessing a big change Oman is not far away from this reality This study aims to gauge into the present tourism status of Oman and its prospects It will examine the pervasiveness of new media and its increasing significance in holding the desired position in the world-class tourism Observation and survey methods are applied to reach out the result Total 125 samples have been collected through an online created link from Salalah to understand the mass thinking about new media and its changing role in the tourism sector The findings provide insight understanding about the current situation of tourism despite all efforts of Tourism Ministry and increasing penetration of new media more efforts and awareness are required in terms of the involvement of locals to make Oman international tourism destination
Keywords: marketing tool; new media; online marketing; tourism; visual effect etc